Teaching English Grammar in Grade X SMKN 1 Tapaktuan - Yulita Halim (Educational Journal, 2026)
Grammar plays a crucial role in supporting language skills, including listening, speaking, reading, and writing. This study aims to explore the approaches used in teaching grammar in grade X SMKN 1 Tapaktuan  through a qualitative reflective design. Data were collected through reflective journals, classroom observations, and thematic notes, and analyzed using thematic analysis. The findings reveal that two main approaches were employed: focus on forms and focus on form. The focus on forms approach was effective in improving students’ grammatical accuracy through explicit instruction and structured exercises. In contrast, the focus on form approach enhanced students’ communicative fluency by integrating grammar into meaningful and context-based tasks. The study further found that a combination of both approaches provided a more balanced development of accuracy and fluency, particularly in vocational contexts where language use is closely related to professional communication. These findings suggest that grammar instruction in  should not rely on a single approach but rather integrate explicit teaching with contextualized practice. This study contributes to the field of English language teaching by highlighting the importance of context-sensitive grammar instruction that aligns with students’ vocational needs